Formative usability evaluation of a fixed-dose pen-injector platform device - Lange J (Dove Medical Press, 2018)
Jakob Lange, Tobias Nemeth Ypsomed AG, Burgdorf, Switzerland Background: This article for the first time presents a formative usability study of a fixed-dose pen injector platform device used for the subcutaneous delivery of biopharmaceuticals, primarily for self-administration by the patient. The study was conducted with a user population of both naïve and experienced users across a range of ages. The goals of the study were to evaluate whether users could use the devices safely and effectively relying on the instructions for use (IFU) for guidance, as well as to benchmark the device against another similar injector established in the market. Further objectives were to capture any usability issues and obtain participants’ subjective ratings on the properties and performance of both devices.Methods: A total of 20 participants in three groups studied the IFU and performed simulated injections into an injection pad.Results: All participants were able to use the device successfully. The device was well appreciated by all users with, maximum usability feedback scores reported by 90% or more on handling forces and device feedback, and by 85% or more on fit and grip of the device. The presence of clear audible and visible feedbacks upon successful loading of a dose and completion of injection was seen to be a significant improvement over the benchmark injector.Conclusion: The observation that the platform device can be safely and efficiently used by all user groups provides confidence that the device and IFU in their current form will pass future summative testing in specific applications. Keywords: human-factor engineering, pen injector, handling study, user error, instructions for use, FixPen